(untitled) (Journal of Engineering, 2008)
The potential to remove Pb(II) from aqueous solutions through biosorption using four raw dead plant biomasses (karab, bardie, rice hulls and corn-cobs) was investigated in batch tests and compared with that for the PAC. From tests, it was found that the four types of dead-plant biomasses had shown high removal efficiency with the descending order (karab, bardie, rice hulls and corn cobs). Their percent removal (% R) of Pb(II) were (98.76, 96.10, 95.16 and 94.70) respectively at pH 4 with 0.2 g of sorbent/100 ml of 10 ppm lead solution , while it was (99.8 %) for PAC. Generally through batch system at a laboratory scale, karab has proved to be an efficient biosorbent for the removal of Pb(II) from aqueous solutions with low initial ion concentration (1–10 mg Pb(II)/ℓ) at pH (4 - 4.5). The EPA discharge limit (0.1 ppm) for lead was achieved. The biosorption rate is quite rapid and within 5 min of mixing more than 90 % of Pb(II) ions were removed by the karab biomass. Varying agitation speed has no influence on the rate of uptake and the Pb(II) uptake was not affected by karab particle size. The Freundlich and Langmuir isotherms described the data well. According to the evaluation using Langmuir equation, the maximum capacity q max obtined from equilibrium biosorption isotherm test was 13.2 mg/l for pb (II) . The ultimate sorption capacity KF in the Frendlich model was 3.1 .